2018
DOI: 10.1016/j.heliyon.2018.e00695
|View full text |Cite
|
Sign up to set email alerts
|

The role of zyxin in regulation of malignancies

Abstract: Focal adhesions are highly dynamic multi-protein complexes found at the cell surface and effectively link the cell's internal cytoskeleton to a complex mixture of macromolecules known as the extracellular matrix and mediate transmission of signals from the extracellular matrix to the nucleus. Zyxin is one of the key focal adhesion proteins and is also found to shuttle in the nucleus. Although the mechanism of shuttling to the nucleus unclear, it moves out from the nucleus through a leucine-rich nuclear export … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…6 ) 42 48 . This is in agreement with observations that zyxin influences cell migration, adhesion and proliferation as well as its potential involvement in cancer progression 49 53 . Zyxin’s role in regulating cell survival is controversial 27 30 , but nuclear activities have generally been related to anti-apoptotic effects 15 , 16 .…”
Section: Discussionsupporting
confidence: 93%
“…6 ) 42 48 . This is in agreement with observations that zyxin influences cell migration, adhesion and proliferation as well as its potential involvement in cancer progression 49 53 . Zyxin’s role in regulating cell survival is controversial 27 30 , but nuclear activities have generally been related to anti-apoptotic effects 15 , 16 .…”
Section: Discussionsupporting
confidence: 93%
“…The research carried out in recent years has confirmed the contribution of ZYX to the development of various cancer types, including melanoma, ovarian, breast, glioma, lung, and oral squamous cell carcinoma (6,(24)(25)(26)(27)(28). Recent observations have revealed that ZYX can act as an oncoprotein or a tumour suppressor, depending on the cancer type (16).…”
Section: The Role Of Zyxin In Carcinogenesismentioning
confidence: 83%
“…This hypothesis was proposed when the interaction of ZYX with E6 protein of human papilloma virus 6 (HPV6) was found (65). As it is commonly known, HPV is responsible, inter alia, for the genital warts and leads to cancer development (16,65). It was demonstrated that the interaction of ZYX with a viral molecule causes its translocation into the nucleus.…”
Section: The Role Of Zyxin In the Development Of Other Cancer Typesmentioning
confidence: 99%
“…Our results demonstrated a decline in the phosphorylated RB levels upon miR-200c and Par-4 overexpression, which could adequately contribute to their pro-apoptotic effects. Zyxin is a crucial focal adhesion protein, and its involvement is reported in many cancers [ 55 ]. Recently, it has been demonstrated to promote cell migration and invasion [ 38 , 56 ].…”
Section: Discussionmentioning
confidence: 99%